2009
DOI: 10.1111/j.1440-1746.2008.05569.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound guided fine needle aspiration of solid pancreatic lesions: Performance and outcomes

Abstract: Our experience confirms that EUS-FNA in patients with suspected solid pancreatic lesions is safe and has a high diagnostic accuracy. This technique should be considered the preferred test when a cytological diagnosis of a pancreatic mass lesion is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 51 publications
2
53
0
7
Order By: Relevance
“…Maguchi et al [13] reported that the tumor detection rate of TS1 pancreatic carcinoma (≤2 mm) was 100%. Diagnosis by EUS-guided fine needle aspiration (EUS-FNA) at the time of tumor detection had a sensitivity of 85% to 94%, a specificity of 100%, and an accuracy of 95% [14] [15]. However, we should keep in mind that the accuracy would be lower for tumors ≤ 1 mm [16].…”
Section: Discussionmentioning
confidence: 99%
“…Maguchi et al [13] reported that the tumor detection rate of TS1 pancreatic carcinoma (≤2 mm) was 100%. Diagnosis by EUS-guided fine needle aspiration (EUS-FNA) at the time of tumor detection had a sensitivity of 85% to 94%, a specificity of 100%, and an accuracy of 95% [14] [15]. However, we should keep in mind that the accuracy would be lower for tumors ≤ 1 mm [16].…”
Section: Discussionmentioning
confidence: 99%
“…EUS-guided FNA and FNB are safe and accurate techniques for the cytohistological evaluation of solid pancreatic lesions (13)(14)(15)24,25,28). The use of reverse-beveled Procore™ needles provides a high diagnostic yield in this setting (17)(18)(19)29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of tissue acquisition via EUS in solid pancreatic lesions has had a major impact on the diagnosis and subsequent management of pancreatic cancer (8)(9)(10)(11)(12). Moreover, EUS-guided fine needle aspiration (FNA) or biopsy (FNB) is safe and reliable (13)(14)(15). Data on the role of EUS-FNB in early CP are scarce (16).…”
Section: Introductionmentioning
confidence: 99%
“…They ob ser ved sen si ti vity, spe ci ficity, po si ti ve pre dic ti ve va lu e, ne ga ti ve pre dic ti ve va lu e, ac cu racy and fal se-ne ga ti ve ra te of en dos copic ul tra so und-gu i ded fi ne-ne ed le as pi ra ti on biopsy as 94.3%, 100%, 100%, 72.2%, 95% and 5%, res pec ti vely. 15 FNAB is valuable in the di ag no sis of PPL. In most of the pa ti ents, the di ag no sis can be es tab lis hed wit ho ut sur gery.…”
Section: Discussionmentioning
confidence: 99%